Sexual Citizenship and the Civil Union Act 2004 - Seuffert, Nan (Victoria University of Wellington Law Review, 2006)
This article analyses the parliamentary debates on the Civil Union Act 2004, which provides for legal recognition of same sex relationships, for stories of national identity. A close reading of the parliamentary debates on the Act suggests that although the supporters and opponents of the legislation seemed to be worlds apart, many told similar stories about New Zealand as a nation, and citizens within that nation, emphasising similar values and aspirations. Both sides told stories of citizens, of New Zealanders, as tolerant and fair, as forwarding-looking progressives who value stable long-term, committed relationships, warm loving communities for children, and strong families and family relationships. Both sides generally saw marriage as a positive institution, a cornerstone of society and a building block for society and the nation. While some talked of existing alternatives to marriage, such as de facto relationships, and there was some recognition that not all marriages are good ones, with a few notable exceptions, there was little mention of critiques of marriage as an institution and little or no positive mention of relationships outside of the paradigm of long-term committed, monogamous relationships. Further, while there were arguments, reflecting a privatisation paradigm, that the Civil Union Act 2004 was not necessary since the rights and duties of same sex couples could be structured using the private law of contract and trusts (a claim that was debated), there was no suggestion that state recognition of marriage should be abolished, or that long-term heterosexual relationships should be structured through private law.